2019
DOI: 10.1002/jctb.6101
|View full text |Cite
|
Sign up to set email alerts
|

Reactor design as a critical input in the electrochemical production of peroxoacetic acid

Abstract: BACKGROUND In the present work, the influence of the most critical inputs affecting reactor design for the simultaneous electrochemical production of peroxoacetic acid (PAA) and hydrogen peroxide are studied. Based on our previous findings, we studied the role of the ratio between the volume of the solution (related to the chemical equilibrium between PAA and hydrogen peroxide) and the intensity (related to the rate and efficiency of the electrochemical processes) for a reactor equipped with a boron‐doped diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Initially, most of these oxidants involved in the decomposition of ozone share the -O-Ogroup and will be denoted in this work simply as peroxo species (named in the mathematical model as 𝑆 3 ), because a full characterization will be pointless as they are known to react fast with ozone once formed and hence, they cannot be properly determined from an analytical perspective. It is important to state that to the best of the authors' knowledge, the decrease observed in the production of ozone is not noticed in previous studies, which focused on the production of peroxosalts [27][28][29]34,35], ferrates [36], total chlorinated oxoanions [37,38] or any other oxidant, and it indicates that ozone electrogeneration is a much more complex process. The kinetics of this process should depend on the concentration of this predator species and also on the concentration of ozone, and can be represented by Eq.…”
Section: Resultsmentioning
confidence: 82%
“…Initially, most of these oxidants involved in the decomposition of ozone share the -O-Ogroup and will be denoted in this work simply as peroxo species (named in the mathematical model as 𝑆 3 ), because a full characterization will be pointless as they are known to react fast with ozone once formed and hence, they cannot be properly determined from an analytical perspective. It is important to state that to the best of the authors' knowledge, the decrease observed in the production of ozone is not noticed in previous studies, which focused on the production of peroxosalts [27][28][29]34,35], ferrates [36], total chlorinated oxoanions [37,38] or any other oxidant, and it indicates that ozone electrogeneration is a much more complex process. The kinetics of this process should depend on the concentration of this predator species and also on the concentration of ozone, and can be represented by Eq.…”
Section: Resultsmentioning
confidence: 82%
“…A similar synthesis for performic acid (PFA) via H 2 O 2 originating from GDEs was described by Kolyagin et al in 2010 . Further studies also employed GDEs for the indirect electrochemical synthesis of PAA via H 2 O 2 , and one study even showed the formation of perbutyric acid. However, studies providing an overview and comparison of different peracids synthesized indirectly on GDEs are still lacking.…”
Section: Introductionmentioning
confidence: 91%
“…5, the complete depletion of oxyfluorfen was achieved in all cases, although the electric charge required slightly depended on the current density applied: approximately 22 Ah L -1 in the case of working at 10 mA cm -2 and approximately 26 and 35 Ah L -1 in the case of using 30 and 100 mA cm -2, respectively. The increase of the electric charge required when increasing the current density applied could be explained by the inefficiencies and side reactions taking place when operating at high current densities (Llanos et al, 2019).…”
Section: Electrochemical Treatmentmentioning
confidence: 99%